2021
DOI: 10.1098/rsif.2021.0421
|View full text |Cite
|
Sign up to set email alerts
|

Enthesis strength, toughness and stiffness: an image-based model comparing tendon insertions with varying bony attachment geometries

Abstract: Tendons of the body differ dramatically in their function, mechanics and range of motion, but all connect to bone via an enthesis. Effective force transfer at the enthesis enables joint stability and mobility, with strength and stiffness arising from a fibrous architecture. However, how enthesis toughness arises across tendons with diverse loading orientations remains unclear. To study this, we performed simultaneous imaging of the bone and tendon in entheses that represent the range of tendon-to-bone insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Specifically, toe modulus and transition stress of slow stretch constructs were 3 to 4-fold higher than cyclic load and static constructs, while all constructs maintained a similar transition strain. In tendons and ligaments, the toe region is attributed to collagen fiber and fibril uncrimping or to the realignment of collagen fibers and fibrils during loading [4,5,30,52,53]; whereas in the enthesis, the toe region is attributed to fiber recruitment and the interactions of the fibers with the bone-ridge of enthesis attachments [54]. In slow stretch constructs, fibrils and fibers in the transition region are already oriented in the direction of the applied uniaxial tensile strain at the start of mechanical testing thus allowing for earlier recruitment and increased toe region stress.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, toe modulus and transition stress of slow stretch constructs were 3 to 4-fold higher than cyclic load and static constructs, while all constructs maintained a similar transition strain. In tendons and ligaments, the toe region is attributed to collagen fiber and fibril uncrimping or to the realignment of collagen fibers and fibrils during loading [4,5,30,52,53]; whereas in the enthesis, the toe region is attributed to fiber recruitment and the interactions of the fibers with the bone-ridge of enthesis attachments [54]. In slow stretch constructs, fibrils and fibers in the transition region are already oriented in the direction of the applied uniaxial tensile strain at the start of mechanical testing thus allowing for earlier recruitment and increased toe region stress.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, based on a series of experiments and models on the mouse supraspinatus tendon insertion, Golman et al have elucidated that differential recruitment of collagen fibers enables toughness across broad loading directions as they have observed that insertion behavior, including strength and stiffness, varied with the angle of abduction, alongside with changes in microscale fiber engagement . Using a mathematical model, the authors further demonstrated that toughness arose from fiber reorientation, recruitment and rupture, mediated by interactions between fibers at the enthesis and the bony ridge abutting it …”
Section: Biomechanicsmentioning
confidence: 99%
“…84 Using a mathematical model, the authors further demonstrated that toughness arose from fiber reorientation, recruitment and rupture, mediated by interactions between fibers at the enthesis and the bony ridge abutting it. 102 The movement of individual fibers and fibrils and the reorientation and recruitment of collagen fibers may all have something to do with fiber orientation and dispersion, and are vital to the insertion biomechanics. Research on other tissue structures has proved that collagen fiber orientation and dispersion govern the ultimate tensile strength, stiffness, and fatigue performance of bovine pericardium.…”
Section: Biomechanicsmentioning
confidence: 99%
“…Depending on the anatomical location, entheses appear either as fibrous or fibrocartilaginous, showing different structural and mechanical properties [ 1 ] . In fibrous insertions, T/Ls attach directly to bones with a 45 degrees angle of incidence [ 2 , 3 ] . Fibrocartilaginous entheses are more complex and more relevant from the clinical point of view.…”
Section: Introductionmentioning
confidence: 99%